English-Polish contrastive grammar at Polish universities - Mańczak-Wohlfeld, Elżbieta (LingBaW. Linguistics Beyond and Within, 2016)
Although contrastive studies do not enjoy great prestige among linguists, they have a very long tradition dating back to ca. 1000 A.D. when Ælfric wrote his Grammatica, a grammar of Latin and English. Even then he must have been aware of the fact that the knowledge of one language may be helpful in the process of learning another language (Krzeszowski 1990). Similarly, it seems that throughout the history of mankind teachers of a foreign language must have realized that a native and foreign tongue can be contrasted. However, contrastive linguistics only came into being as a science at the turn of the 19th and 20th centuries. The first works were almost purely theoretical, and it is worth emphasizing that among the first scholars working in the field was Baudouin de Courtenay, a Polish linguist, who published his contrastive grammar of Polish, Russian and Old Church Slavonic in 1912. The outbreak of the Second World War was a milestone in the development of applied contrastive studies since a need to teach foreign languages in the United States arose as a result. The 1960’s is considered a further step in the development of contrastive grammar since a number of projects were initiated both in Europe and in the U.S.A. (Willim, Mańczak-Wohlfeld 1997), which resulted in the introduction of courses in English-Polish contrastive grammar at Polish universities. The aim of the present paper is to characterize and evaluate the courses offered in the English departments of selected Polish universities and to suggest an “ideal” syllabus.